2021
DOI: 10.3389/fchem.2021.685014
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Development of Ceramic-Graphene Based Nanohybrid Composite Systems in Biological Applications

Abstract: Graphene-based nanocomposites constitute an interesting and promising material for various applications. Intensive progress in the development of this group of materials offers an opportunity to create new systems useful for drinking water decontamination or other biotechnological applications. Nanohybrid structures of graphene-ceramic systems can be obtained using covalent graphene surface modification with nanoparticles (NPs) of ceramic and/or co-deposition of metals with selected morphology and chemistry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 124 publications
(205 reference statements)
0
3
0
Order By: Relevance
“…Jakubczak et al [41] reported RGO/Al2O3-Ag nanocomposite with surface modification of metal oxide nanoparticles (MxOy) onto graphene family nanomaterials (GFMs) for filtration of drinking water. Figure 6 illustrates the chemical modification of graphene materials for water filtration properties.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Jakubczak et al [41] reported RGO/Al2O3-Ag nanocomposite with surface modification of metal oxide nanoparticles (MxOy) onto graphene family nanomaterials (GFMs) for filtration of drinking water. Figure 6 illustrates the chemical modification of graphene materials for water filtration properties.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…The addition of sawdust in the clay has shown to improve bacterial removal efficiencies. Therefore, it is predicted from the results that the composite material has great surface adsorption activity and biocidal activity which resulted in 99% reduction of bacteria from water [25].…”
Section: Microbial Removalmentioning
confidence: 99%
“…In most of these applications, the 2D structured graphene nanosheets are necessary to be combined with bulk materials such as polymers, ceramics, or metals. Consequently, they form, for example, by mixing applicable composites or by deposition or printing modified surfaces of layered 3D devices [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%